(3EjVGM GdeYGfi GdedgeGJ HTQM efXheI GdehLgGJs - (3eMeO GdMOjfi GdOefghQis; (3eUWaj GdHOQj , eUWaj GdHOQj GdOejGWj GdTGaYj,J (B1293 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd eMeO GdMOjfi GdOefghQi Ph GdeBKe hGdChRGQ s
(3BNQgG (B:s
(3GdJhQjN JYQja GdhbJ Jbhd CQN GdcJGH Hjhe cPG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdadSaI hGdefWbs